Asessment of risk management in government construction project - Athirah Izzati, Zakaria (2018)
Klang Valley is one of the flood prone areas where flash floods often hit several areas in Klang Valley following the heavy downpour. Due to the unexpected climate change, it will likely result in an increase in the intensity and frequency of extreme precipitation events in most regions in the future. The rainfall Intensity-Duration-Frequency (IDF) relationship is one of the most commonly used tools in water resources engineering, either for planning, designing and operating of water resource projects, or for various engineering projects against floods. The data in IDF curve is not consistence for every year because of Malaysia climate always change. Besides, urban drainage systems often cannot cope with intense convective rainfall events. Other than that, in MSMA2 the data only represent for major towns. This means that there is a large potential error in extrapolating to long ARI such as 100 years. Thus a new and updated IDF curve is needed to make as a reference to design drainage and storm water management. The purpose of this study is to develop the fittings constants based on the intensity duration frequency (IDF) using frequency analysis such as Gumbel distribution and Log-Normal distribution in Klang Valley. The empirical formula that is used to estimate the fitting constant of IDF curve is Sherman Equation. Besides, it is to analyze the rainfall intensity values between MSMA2 and estimated fitting constants of IDF curve in Klang Valley using Sherman Equation. The Sherman Equation is used to computed the locality constants which are a,b and c. The overall percentage different of Sherman Equation and MSMA 2 for Gumbel distribution function is from 0% until 3200% while the percentage different of Sherman Equation and MSMA 2 for Log Normal distribution function is from 0% until 1000%. Based on the results, Log Normal distribution is more suitable and reliable for Klang Valley when compared to Gumbel distribution as the percentage different of Sherman Equation and MSMA 2 for Log Normal distribution is smaller than Gumbel distribution.